Cardiovascular Risk Factors Associated with Mitral Annular Calcification in a Non-Rheumatic Population: Cardiovascular Risk Factors - Rehman, Mahboob ur; Faisal, Muhammad; Ali, Anwar; Iqbal, Mohmmad; Rauf, Asma; Abrar, Amjad (Pakistan Journal of Health Sciences, 2024)
Mitral Annular Calcification (MAC), cardiovascular disease marker was common in non-rheumatic populations but was frequently disregarded in clinical evaluations. Objective: To MAC and to assess effect of these factors on cardiac function in non-rheumatic adult population. Methods: From September 2022 to August 2023, we conducted this cross-sectional study at Cardiac Center, Pakistan institute of medical sciences Islamabad that included 182 adults aged 50 years and older. We evaluated the patient's clinical history, demographic data and echocardiographic and laboratory results. The association between the presence of MAC and cardiovascular risk factors (age, hypertension, diabetes, dyslipidemia, smoking, obesity and chronic renal disease) was analyzed using logistic regression. Echocardiographic data were used to provide insight into cardiac function. Results: The prevalence of MAC was substantially correlated with hypertension (OR = 2.30), diabetes (OR = 2.00), dyslipidemia (OR = 1.75) and obesity (OR = 1.07). Also, smoking demonstrated a significant correlation with MAC. In comparison to those without MAC, individuals with MAC exhibited substantially lower ejection fractions, increased left atrial diameters and impaired diastolic function, as indicated by cardiac function assessments. Conclusion: In non-rheumatic population, MAC was significantly associated with conventional cardiovascular risk factors, particularly hypertension and diabetes.